A71 ANTI-SACCHAROMYCES CEREVISIAE ANTIBODIES AS A PROGNOSTIC BIOMARKER IN CHILDREN WITH CROHN'S DISEASE. (15th March 2019) - Chandrakumar, A; Georgy, M; Agarwal, P; 't Jong, G; EL-MATARY, W
Abstract: Background: Inflammatory bowel disease (IBD) is a collective term for diseases involving inflammation of the gastrointestinal tract, among which Crohn's disease (CD) and ulcerative colitis (UC) are the two main sub-categories. Although Anti-Saccharomyces cerevisiae antibodies (ASCA) could be a useful biomarker in differentiating CD from ulcerative colitis UC, their role as prognostic markers in children with CD has been under-investigated. Aims: Our longitudinal study aimed to assess the stability of ASCA status over time and the possibility of an association between ASCA-positive childhood CD and disease relapse during clinical follow-up. We also investigated the role of ASCA status as a prognostic marker of response to Anti-TNF biological therapy among children with CD. Methods: The study population comprised of children with inflammatory bowel disease (IBD) diagnosed with CD from 2012 to 2018. Cox-regression model with adjustment for a priori covariates was used to examine the risk of disease relapse and response to biological therapy among ASCA positive patients in comparison to ASCA negative patients. The models were adjusted for age at diagnosis, sex, history of CD in the first-degree relatives, luminal disease distribution at baseline, pharmacological therapy and baseline clinical disease activity. Results: A total of 273 measurements from 72 CD patients (mean age at diagnosis of 12.17±3.17 years), who were followed up for a median duration of 14 months (IQR: 5–42) were included. ASCA positive patients had a higher risk for moderate to severe clinical disease and extensive distribution at baseline in comparison to ASCA negative patients, (odds ratio (OR): 2.88; 95% confidence interval (CI): 1.2–7.55) (OR: 3.30; 95% CI: 1.12–9.74) respectively. In comparison to ASCA IgG negative patients, ASCA IgG positive patients who were treated with biologics had a significantly lower relapse rate (aHR: 0.12; 95% CI: 0.02–0.93). Ten (14%) patients had an unstable ASCA value with either ASCA IgA or ASCA IgG status changing from positive to negative or vice versa. Conclusions: ASCA positive children with CD present with more extensive and clinically severe disease. ASCA IgG is a useful prognostic marker among children with CD who receive biologics. Survival plots for disease relapse during follow-up among biological therapy naïve children with Crohn's disease (a and c) compared to those who were treated with biological therapy (b and d). (adjusted for age at diagnosis, sex, family history of IBD, luminal disease distribution at baseline, non-biologic pharmacological therapy and baseline disease severity) Funding Agencies: Children's Hospital Research Institute of Manitoba